Beyond Chrismukkah : The Christian-Jewish Interfaith Family in the United States - Mehta, Samira K. (Book collections on Project MUSE., 2018)
"Drawing on historical research, ethnography, and original interviews, Beyond Chrismukkah describes and analyzes how interfaith Christian-Jewish families were understood, viewed, and treated in the larger American social milieu from 1965 through the present. [Mehta] shows how during the latter half of the twentieth century, interfaith marriage was subject to much the same dynamic and dramatic change that took place generally in American culture: from 1965 to 2010, the rate of intermarriage for American Jews rose from less than 10% to its current rate of between 40-50%. She argues that the understanding of ethnicity, and, in particular, the turn to multiculturalism in the 1990s, generated significant cultural and political change over time."--